Topic, Focus and Configurationality : Papers from the 6th Groningen Grammar Talks, Groningen, 1984. - Abraham, Werner (John Benjamins Pub. Co., 1986)
Some fundamental questions regarding sentence structure in linguistics concern whether all languages, at some level of abstraction, have the same structure, and what are the basic categories with which to describe sentence structure. The contributors of this volume are specialized in two quite different languages: Hungarian and German. Of the German papers three are mainly about focus (Abraham, Jacobs, and Stechow-Uhman), whereas the remaining ones (Haider and Scherpenisse) are mainly about V-second. The Hungarian papers are all about focus, of which those of Kálman, Kiefer, Marácz, and De Mey.